K. A. Fox, J. K. Sengupta y E. Thorbecke, The Theory of Quantitative Economic Policy with Applications to Economic Growth and Stabilization. vol. 5 de la colección Studies in Mathematical and Managerial Economics. Amsterdam, North Holland, 1966. XXIII, 514 p. - Uribe Jr., Pedro (Estudios Demográficos y Urbanos, 1968)
K. A. Fox, J, K. SENGUPTA y E. THORBECKE, The Theory of Quantitative Economic Policy with Applications to Economic Growth and Stabiíization. Vol. 5 de la colección Studies in Mathematical and Managerial Economics. Amsterdam, North Holland, 1966.